Klasifikasi Rasa Susu Almond Berdasarkan Minat Pelanggan Menggunakan Algoritma C4.5 di Home Made MamiNia Ice Pematangsiantar - Febriani; Indra Gunawan; Rafiqa Dewi; Dedy Hartama; Muhammad Ridwan Lubis (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2021)
Almond milk is a plant-based milk drink made from almonds. Almond juice has a paler color and a thicker texture than regular milk. As for the benefits of almond milk in the world of health, namely to increase breast milk production, prevent high blood pressure, strengthen immunity, protect bone health, maintain baby's heart health, prevent free radicals, facilitate digestion, make skin bright after childbirth. Data mining is part of the Knowledge Discovery in Database (KDD) process stage. Therefore, the authors provide a classification solution in Data Mining is done using the Algorithm C4.5. With the Algorithm C4.5 you will get a Decision Tree that is easy to understand and easy to understand. Thus, it can help the owner determine the almond milk production plan that is most in demand and without worrying about excess goods or shortages of ingredients.